Pengaruh Biochar Sekam Padi dan Macam Pupuk terhadap Pertumbuhan dan Serapan P Padi - Hery Widijanto; Siti Ramadhani Nur Rissanti; Suntoro Suntoro; Jauhari Syamsiyah (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2023)
Inceptisol soil has an acidic pH, low organic content, and low P elements. Biochar and other types of fertilizers are needed to improve soil fertility. This research was conducted to determine the effect of the best dose of biochar and the kind of fertilizer on rice plants' growth and P uptake. There were 16 treatments with 3 repetitions. The dosage of rice husk biochar consists of doses of 0 t.ha-1 (B0), 5 t.ha-1 (B1), 10 t.ha-1 (B2), and 20 t.ha-1 (B3). Types of fertilizer consist of 0 t.ha-1 (P0), 4 t.ha-1 manure (P1), 50% urea + 50% NPK fertilizer + 2 t.ha-1 manure (P2), and 100% urea + 100% NPK fertilizer (P3). Parameters observed were available P, P tissue, P uptake, plant height, number of tillers, and dry weight brazier. Data analysis was performed with the ANOVA, DMRT, and Correlation tests. The result showed the dosage of rice husk biochar and the type of fertilizer affected the yield of rice plant height, number of rice tillers, stover dry weight, and P uptake. P3 treatment produced the highest plant height, which was 104,68 cm. The B3 and P3 treatments produced the highest of rice tillers. The B3P3 interaction treatment resulted in the highest root tissue absorption of 1,93 g.clamp-1 and 3,49. clamp-1 in the mature.